The wisdom of the Christian faith - Moser, Paul K., 1957-; McFall, Michael T., 1978- (Cambridge : Cambridge University Press, 2013)
"The Wisdom of the Christian Faith joins philosophy and New Testament theology to offer a unique product: an anthology of accessible essays by prominent Christian philosophers on topics of religious and philosophical interest"--
"Although typically separated, philosophy and New Testament theology are mutually beneficial for the understanding of the distinctive wisdom that guides Christian thought and life. The Wisdom of the Christian Faith fills a major gap in the literature on the philosophy of religion. It is the first book on the philosophy of religion to be authored entirely by philosophers while directly engaging themes of wisdom in the Christian tradition. The book consists of all new essays, with contributions from John Cottingham, Paul Gooch, Gordon Graham, John Hare, Michael T. McFall, Paul K. Moser, Andrew Pinsent, Robert Roberts, Charles Taliaferro, William Wainwright, Jerry Walls, Sylvia Walsh, Paul Weithman, and Merold Westphal"--
Machine generated contents note: Introduction: philosophy and cruciform wisdom; Part I. Wisdom, Faith, and Reason: 1. Faithful knowing / Paul Gooch; 2. Repentance and self-knowledge / Merold Westphal; 3. Obedience and responsibility / William Wainwright; 4. Forgiveness, justification, and reconciliation / John Hare; Part II. Wisdom, Love, and Evil: 5. Wisdom and evil / Andrew Pisent; 6. Moral character and temptation / Sylvia Walsh; 7. Altruism, egoism and sacrifice / Gordon Graham; 8. Unconditional love and spiritual virtues / Robert C. Roberts; Part III. Wisdom, Contemplation, and Action: 9. Meaningful life / John Cottingham; 10. Beauty and aesthetics in theology / Charles Taliaferro; 11. Education for political autonomy / Paul Weithman; 12. The wisdom of hope in a despairing world / Jerry Walls.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Christianity -- Philosophy; Philosophical theology; Wisdom; Knowledge, Theory of (Religion); Bible. -- Theology; RELIGION / Theology; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books